E-AZS Platform model – the concept of application of information and communications technology in sports enterprises - Cieśliński, Wojciech B.; Witkowski, Kazimierz; Migasiewicz, Juliusz; Rokita, Andrzej; Perechuda, Kazimierz; Chomiak-Orsa, Iwona (Business Informatics, 2014)
The article presents the research concerning the description of the possible application, in sports enterprises, of an ICT system supporting the exchange of data, information and knowledge between the management, trainers providing training services, and the clients of the sports enterprise, namely the athletes
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 9-15
Keywords: ICT platform; process approach; sports enterprise; monitoring of the flow of data; information and knowledge; platforma; procesy; przedsiębiorstwa sportowe; monitorowanie przepływu danych, informacji i wiedzy